Adult-onset Still's disease with atypical cutaneous manifestations. Issue 11 (March 2017) - Narváez Garcia, Francisco Javier; Pascual, María; López de Recalde, Mercè; Juarez, Pablo; Morales-Ivorra, Isabel; Notario, Jaime; Jucglà, Anna; Nolla, Joan M.
Abstract : Abstract: The diagnosis of adult-onset Still's disease (AOSD) can be very difficult. There are no specific tests available, and diagnosis is usually based on a symptom complex and the well-described typical evanescent rash seen in the majority of patients. However, in recent years, other atypical cutaneous manifestations of AOSD have been reported. These atypical skin eruptions often present in addition to the typical evanescent rash but may also be the only skin manifestation, resulting in delayed diagnosis because of under-recognition. In this study, we present 3 new cases of AOSD with atypical cutaneous manifestations diagnosed during a 30-year period in our department and review 78 additional cases previously reported (PubMed 1990–2016). These 81 patients form the basis of the present analysis. The overall prevalence of atypical cutaneous manifestations in our AOSD population was 14%. These manifestations may appear at any time over the course of the disease, and usually occur in patients who have persistent and severe disease, with a considerable frequency of clinical complications (23%), including serositis, myopericarditis, lung involvement, abdominal pain, neurologic involvement, and reactive hemophagocytic syndrome. The most representative and frequent lesion among the nonclassical skin rashes is the development of persistent pruritic papules and/or plaques. Interestingly, these lesions show a distinctive histological pattern. Other, less frequently observed lesions include urticaria and urticaria-like eruptions, generalized or widespread non-pruritic persistent erythema, vesiculopustular eruptions, a widespread peau d'orange appearance of the skin, and edema of the eyelids mimicking dermatomyositis without any accompanying skin lesion. The great majority of these patients required medium or high doses of glucocorticoids (including intravenous methylprednisolone pulse therapy in some cases) and, in nearly 40%, a more potent or maintenance immunotherapy with immunosuppressant drugs and/or biologic agents (mainly anakinra or tocilizumab) to control or manage symptoms because of a polycyclic or chronic course. The development of atypical cutaneous manifestations seems to be associated with a potentially worse prognosis, with a mortality rate reaching 8% primarily because of infectious complications related to immunosuppressive therapy. In conclusion, the appearance of atypical cutaneous manifestations is not uncommon in AOSD. Recognition of this clinical variant is crucial for the early diagnosis of AOSD, as it might imply persistent disease activity and the need for more aggressive treatment.